Peran Model Pendidikan Wustho terhadap Prestasi Belajar Siswa pada SMP PGRI 1 Ciambar Kec. Ciambar Kab. Sukabumi - Amir Mirdad; Siti Qomariyah; Moh. Jujun Sirojudin; Hoerul khusban (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Community-based education is an approach that positions society as an active participant in the educational process, integrating local culture, values, and social dynamics into learning. One such model that reflects these principles is the Wustho educational model, which originates from the Islamic pesantren system. This model offers a balanced integration between religious and general education, emphasizing the role of community and character development as essential elements of student success. This research aims to explore the influence of the Wustho model on students’ academic achievement at SMP PGRI 1 Ciambar, Ciambar Sub-district, Sukabumi Regency. The study involved 150 students across different grade levels, using a qualitative descriptive research approach. Data collection techniques included participatory observation, in-depth interviews with teachers, school leaders, and parents, as well as document analysis of academic performance records.The findings indicate that the implementation of the Wustho model has a positive impact on student achievement, both in academic and behavioral aspects. Students showed improvement in learning motivation, discipline, and active engagement in religious and community-based learning activities.¹ This model also strengthens moral values and spiritual awareness, which in turn enhances students’ holistic learning outcomes.² Moreover, collaboration between schools, families, and community figures plays a crucial role in reinforcing the effectiveness of this educational approach.³ The presence of religious instruction embedded within daily learning experiences helps students to better contextualize academic content in real-life situations.⁴In conclusion, the Wustho educational model offers a meaningful contribution to the development of community-based education practices, especially in rural or religiously active areas. Its focus on moral education, community involvement, and the integration of spiritual and secular knowledge demonstrates its relevance and effectiveness in improving student learning outcomes. It is recommended that similar models be adapted in other educational settings where community values are strongly upheld.